Fluorescent correlation spectroscopy measurements with adaptive optics in the intercellular space of spheroids - Leroux, Charles-Edouard (Optical Society of America, 2014)
In this study we demonstrate the use of adaptive optics to correct the biasing effects of optical aberrations when measuring the dynamics of molecules diffusing between cells in multicellular spheroids. Our results indicate that, on average, adaptive optics leads to a reduction of the 3D size of the point spread function that is statistically significant in terms of measured number of molecules and diffusion time. The sensorless approach, which uses the molecular brightness as optimization metric, is validated in a complex, highly heterogeneous, biological environment. This work paves the way towards the design of accurate diffusion measurements of molecules in thick biological specimens.